Otimização do fluxo de informações por meio do design thinking no setor plataformas e tecnologia da Equatorial Telecom - FACURI, Hudson Carlos Lobato (2024)
This work uses Design Thinking to optimize the flow of information in the platforms and technologies sector at Equatorial Telecom. During the 29th European Regional Conference of the International Telecommunications Society (ITS), the largest European telecommunications forum, the participants highlighted it. The methodology has several applications, such as technical applications, companies' products/services, and core processes. Immersion was carried out, and individual and anonymous interviews were conducted with company participants using Google Forms. The analysis method was through the comparative procedure of the flow of documentation information from the old sector and the new one generated from the information collected with the tools (Brainwriting, effort, and impact matrix for prioritizing causes and possible solutions, 5w2h and the test cards) that construct the execution steps. Among the results obtained, it is essential to accentuate that the scenario before the use of Design Thinking had only 14 flows and activities surveyed by the sector. There were only 14 flows known, and with the activities published in the knowledge base, where there were no prospects for future surveys. After implementing the proposed methodology for a month, the number of flows with activities increased to 29. Out of these, 20 flows and activities were published in the knowledge base, and the construction of the remaining 9 flows and activities is expected to be completed soon. After four months of using Design Thinking, the technology area had already surveyed 110 flows and activities, which interfaced with other sectors. Meanwhile, 104 flows and activities had been published in the knowledge base. The following results were obtained: a) Effective knowledge management with the optimization and standardization of the flow of information from sector documentation to the knowledge base; b) Optimization of activities related to the flow of documentation information; c) Reduction of failures in the execution of activities; d) Reduction of costs with training new employees in the sector; e) Improvement of formal communication in the technology area; f) Development of an application method to optimize the company's internal information flows. In this way, Design Thinking provided more precise diagnoses of problems and proposed solutions that served as suggestions in decision-making. Machado (2016) advocates that Design Thinking can be used in various situations, including the development of more collaborative administrative practices and the creation of solutions to real problems faced by organizations. Given the facts presented, it is concluded that Design Thinking could adhere to the proposed objective, which generated more maturity for the sector and, consequently, for the company that was employed. This work contributed to understanding the application of Design Thinking in optimizing information flows in a technological area. It also presented results that can serve as a basis for decision-making regarding future applications of Design Thinking in optimizing other information flows.